Acute effects of a standardised extract of Hericium erinaceus (Lion’s Mane mushroom) on cognition and mood in healthy younger adults: a double-blind randomised placebo-controlled study - Surendran, Geyan; Saye, Jake; Binti Mohd Jalil, Syahira; Spreadborough, Jack; Duong, Kyle; Shatwan, Israa M.; Lilley, Dash; Heinrich, Michael; Dodd, Georgina F.; Surendran, Shelini (Frontiers in Nutrition, 2025)
IntroductionAnimal studies have suggested that Lion’s Mane mushroom [Hericium erinaceus (Bull.) Pers.] can enhance cognitive function and mood due to its bioactive metabolites, including erinacines and hericenones. However, despite being an ingredient used both culinarily and therapeutically in the East, and more and more commonly in the West, limited research has focused on the immediate effects of H. erinaceus on the cognitive function and mood of healthy young adults.MethodsIn an acute randomized, placebo-controlled, double-blinded, cross-over intervention study, we investigated the potential benefits of an acute dose of H. erinaceus fruiting body extract (3g of 10:1 extract) on cognitive performance and mood compared to a placebo. Eighteen healthy participants aged 18 to 35 years took part in the study. At baseline and 90 minutes post-consumption of the interventions, cognitive and mood assessments were administered to measure various cognitive abilities such as executive function, working memory, psychomotor skills, attention and information processing speed as well as positive and negative affect.Results and discussionThe results showed no significant effect of the H. erinaceus fruiting body extract for composite measures of global cognitive function and mood. However, when analysing individual tests, participants exhibited improved performance on the pegboard test at 90 minutes following a single dose of H. erinaceus.ConclusionIn conclusion, acute consumption of H. erinaceus fruiting body did not demonstrate a significant overall improvement in cognitive performance and mood compared to the placebo and any benefits may be task or domain specific. Further investigations should investigate the effects of chronic supplementation of H. erinaceus fruiting body on cognition and mood in healthy younger adults, as well as establish optimal dosage and the time to peak concentration of H. erinaceus bioactives in the human brain. Additionally, future research should aim to further elucidate potential mechanisms of action to explain potential brain region and cognitive domain specific effects, such as possible regional increases in cerebral blood flow following consumption of H. erinaceus fruiting bodies. It must also be noted that typically only Lion’s mane fruiting bodies are consumed culinarily, where up to 300g of fresh fruiting body are often consumed in the form of mushroom steaks.